Bioproduct with plastic digester potential. The teaching of environmental ethics by the project SAPB-LIPAT/UFRJ & UNIFASE-FMP - Filho, Fernando Coutinho Cruz; Silva , Felipe Freire Souza; Bellizzi , Gabriela Miranda; Silva, Isabela de Souza Ramos; Gaspar , Sandra Ávila; Gorini , Claudia Correia; Pyrrho , Alexander dos Santos; Varricchio , Marcia Cristina Braga Nunes (Seven Editora, 2023)
This chapter traces the historical trajectory of teaching via the hidden curriculum of bioethics, plant biotechnology, phytotherapy and homeopathy through the partnership between the university center UNIFASE-FMP and the Environmental Health, Parasitology, Bioethics Project of the Immunoparasitology and Toxicological Analysis Laboratory of the Faculty of Pharmacy at UFRJ. Through scientific initiation activities, rational skills were developed for thinking aimed at solving sustainability problems with raw plant extracts and ultra-diluted and energized solutions. In parallel, the development of cultural competence and competence in environmental ethics. Actions in primary health care via health education and health promotion were carried out. As a result of scientific initiation investigations, bioproducts showed potential as resources for sustainability, especially one of them with very promising plastic digester potential. We declare that there are no conflicts of interest. This path of innovative teaching focused on environmental ethics at graduation and Medical Residency is in line with the new code of medical ethics and the concept of environmental health. This gathering of concepts and practices represents an advance in contemporary science, integrating knowledge and knowledge, towards complexity. DOI:https://doi.org/10.56238/interdiinovationscrese-069